Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae) - Prado, André Wanderley Do; Baptista, Renner Luiz Cerqueira; Machado, Miguel (Zootaxa, 2018)
The genus Epicadinus Simon, 1895 can easily be distinguished from the other Neotropical Stephanopines by their abundant and robust setiferous tubercles, topped by elongated macrosetae, which cover most of the tegument. Additionally, the genus can be recognized by a pair of conical ocular mounds above the ALE, the anterior eye row very recurved, posterior one slightly procurved; carapace flattened and without tubercles, and opisthosoma with three conical projections (“tubercles”) of variable size and shape. This work is a taxonomic review of the 12 valid species of Epicadinus as listed in version 19 of the World Spider Catalogue (2018), whose hitherto known distribution included few records from Brazil, French Guiana, Bolivia and Peru, and only one from Mexico. Four valid species are recognized: Epicadinus biocellatus Mello-Leitão, 1929; E. trispinosus (Taczanowski, 1872) [with two junior synonyms E. trifidus (Pickard-Cambridge, 1893) syn. nov. and E. cornutus (Taczanowski, 1872) syn. nov.]; E. spinipes (Blackwall, 1862) [with two junior synonyms E. albimaculatus Mello-Leitão, 1929 syn. nov. and E. gavensis Soares, 1946 syn. nov]; and E. villosus [with two junior synonyms E. helenae Piza, 1936 syn. nov. and E. marmoratus Mello-Leitão, 1947 syn. nov.]. Epicadinus polyophthalmus Mello-Leitão, 1929 and Epicadinus tuberculatus Petrunkevitch, 1910 are transferred to Epicadus. Epicadus polyophthalmus (Mello-Leitão, 1929) comb. nov. is considered a nomen dubium. Epicadus tuberculatus (Petrunkevitch, 1910) comb. nov. is a senior synonym of Epicadus pustulosus (Mello-Leitão, 1929) syn. nov.